2019
DOI: 10.1088/1758-5090/ab0cf6
|View full text |Cite
|
Sign up to set email alerts
|

3D printing of complex GelMA-based scaffolds with nanoclay

Abstract: Photo-crosslinkable gelatin methacrylate (GelMA) has become an attractive ink in 3D printing due to its excellent biological performance. However, limited by low viscosity and long cross-linking time, it is still a challenge to directly print GelMA by extrusion-based 3D printing. Here, to balance the printability and biocompatibility, biomaterial ink composed of GelMA and nanoclay was specially designed. Using this ink, complex scaffolds with high shape fidelity can be easily printed based on the thixotropic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
155
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(158 citation statements)
references
References 31 publications
2
155
0
1
Order By: Relevance
“…1F). All these results suggested that both mechanical and oriented gradients could be regulated through tuning multiple factors simply, superior to gradient hydrogel systems reported previously (Wang et al, 2018b;Yang et al, 2018;Gao et al, 2019). The mechanical gradients of the hydrogels could be cover different tissues including skin, muscle, cartilage and bone, suggesting their promising applications across these tissues (Nonoyama et al, 2016;Oh et al, 2016;Lu et al, 2018;Yin et al, 2018).…”
Section: Research Articlementioning
confidence: 80%
See 2 more Smart Citations
“…1F). All these results suggested that both mechanical and oriented gradients could be regulated through tuning multiple factors simply, superior to gradient hydrogel systems reported previously (Wang et al, 2018b;Yang et al, 2018;Gao et al, 2019). The mechanical gradients of the hydrogels could be cover different tissues including skin, muscle, cartilage and bone, suggesting their promising applications across these tissues (Nonoyama et al, 2016;Oh et al, 2016;Lu et al, 2018;Yin et al, 2018).…”
Section: Research Articlementioning
confidence: 80%
“…These approaches usually need special apparatus and rigorous parameters and are only feasible for specific materials. Photopatterning is also used widely to introduce both physical and chemical gradients in which photoresponsivity is a prerequisite for the treated systems (Gao et al, 2019). Recently, buoyancy-driven gradients of various cargos were achieved for different biomaterials, suggesting a more versatile strategy of fabricating bioactive biomaterials used in complex tissue regenerations (Li et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gelatin combined with other hydrogels has been used to optimize printability, improving shape retention during printing. For example, gelatin-alginate [240,[319][320][321], Laponite [322], nanoclays [323], and synthetic polymers such as Pluronic F-127 [208] and PCL [324], have all been studied. Alginate dialdehyde-gelatin scaffolds were printed in the presence of a cross-linker for reaching feature sizes of~500 µm [245], while alginate-GelMA interpenetrating networks via UV crosslinking of GelMA followed by Ca crosslinking of alginate was reported [321].…”
Section: Structural and Mechanical Propertiesmentioning
confidence: 99%
“…Inclusion of alginate [240,[319][320][321], Laponite [322], nanoclays [323], Pluronic F-127 [208], PCL [324]; Feature size 500 µm [245] [ [313][314][315][316]; Feature size 300 µm (SLA), Compressive E: 0.5-18 MPa [328] Mouse planta dermis [319]; dental pulp stem cells [320]; hMSCs and amniotic epithelial cells [240]; chondrocytes [214,327] Silk ( Mouse articular chondrocytes [342]; human fibroblasts [338]; porcine chondrocytes [340]; hMSCs [344,345]; human mesenchymal progenitor cells [346]…”
Section: ) Applicationsmentioning
confidence: 99%